Street art und die demokratisierung der Kunst in Berlin - Dore, Fernanda, author; Bodine, Jay, advisor; Kirby, Rachel, committee member; Moseman, Eleanor, committee member (Colorado State University. Libraries, 2012)
Graffiti, Post-Graffiti, Urban Art and Street Art are sometimes used as synonyms. Authors in the field of Street Art agree that this art form derives directly from the subway graffiti in New York, and often designate it as an art movement. This work defends the thesis that the more the art on the Berlin Wall increased the tolerance towards and integration of the art in the public spaces, the more it contributed to the popularization of the contemporary Street Art in Berlin. The goal of this paper is trifold: 1. to clarify the relationship between the Street Art in Berlin today and the art on the Berlin Wall; 2. to understand the institutionalization of this art form; and 3. to bring light to the democratization of art through Street Art in Berlin. With this purpose, I will analyze the efforts that differentiate Berlin from other cities and position Street Art not as vandalism, but rather as a part of the art in public spaces. The essence of this art form derives from site-specific art, whereby the place plays an inherent part in the artwork. These qualities can be recognized in the Street Art in Berlin from the 70's until today, and its popularization is deeply connected with the German cultural politics of the 70's and the historical significance of the Wall Art. In addition, Street Art challenges the paradigms between high and low art, as well as the contemporary role of the museum. The consequences of the institutionalization of this art form are its democratization and commodification. Finally, Street Art can be considered responsible for a Musealization from Below, whereby the place (the walls of the metropolis) becomes part of the work and its cultural, historical and identity values are emphasized. This is particularly true in the case of the Berlin Wall. Street Art is site-specific, because the works give the place a new meaning and vice-versa. Instead of simulating Street Art in an institutional space, the projects in Berlin attempt to transform the street into an art gallery, inserting the art into the life of the people and finally contributing to the democratization of art.
Street art and the democratization of art in Berlin
Text in German; title and abstract in English and German.
Keywords: Berlin; Berliner Mauer; graffiti; identität; Mauerkunst; street art